Pronominalization and clitic doubling in Syrian and Omani Arabic - Hallman Peter; Al-Balushi Rashid (Linguistics)
This article treats cliticization of a pronoun to a syntactic host and doubling of the clitic pronoun with a non-pronominal counterpart in Syrian and Omani Arabic. Although the two varieties are closely related and the morphological paradigms they display are very similar, the pronominalization and clitic pronoun doubling patterns they display are quite different. We trace this difference to a basic difference in whether the relevant syntactic processes are sensitive to intervention effects in the two dialects, with the result being that the restrictiveness of pronominalization and clitic pronoun doubling patterns parallel the restrictiveness of basic word order patterns – whether double-object constructions are ‘symmetric’ or ‘asymmetric’ – with Syrian being the more restrictive of the two varieties.